A method for manufacturing a substrate-free, flexible photodetector
Patent Information
- Application Number
- CN202311520396.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-15
AI Technical Summary
传统柔性光电探测器的制备工艺复杂,难以在复杂形貌表面实现高效结合,且传统材料在生物相容性和器件性能上存在限制。
A substrate-free, flexible photodetector was fabricated by doping MoS2 nanosheets into a polyvinyl alcohol (PVA) solid electrolyte using liquid phase exfoliation, water bath heating, and vacuum degassing.
The fabrication process was simplified, the cost was reduced, and a substrate-free, flexible photodetector with good optoelectronic properties was obtained, which is suitable for flexible electronic devices and wearable devices.
Smart Images

Figure HDA0004550314530000011 
Figure HDA0004550314530000012 
Figure HDA0004550314530000021
Abstract
Description
Technical fields:
[0001] This invention belongs to the field of new inventions, specifically relating to a substrate-free, flexible photodetector device based on MoS2 nanosheets, polyvinyl alcohol (PVA), and ethylene glycol. Background technology:
[0002] In recent years, the demand for developing next-generation electronic applications has been growing, such as bio-integrated sensors and flexible portable devices. These applications place new demands on semiconductor materials with unique mechanical, optical, and electrical properties. Meanwhile, the rigidity and brittleness of traditional rigid electronic devices make bonding with complex surface morphologies difficult, limiting their application scope. For example, mechanical mismatch and chemical differences between rigid electronic devices and biological tissues can significantly affect biocompatibility and device performance, and have adverse effects on the soft tissues in contact with them. Therefore, researchers are actively exploring various novel material forms such as nanofilms and nanosheets. Among these, nanosheet materials possess many superior properties, including excellent electrical and optical properties and good mechanical flexibility, enabling their application in the production of flexible devices with specific functions.
[0003] Compared to traditional rigid devices, flexible photodetectors possess advantages such as deformation resistance, adaptability to soft surfaces, mechanical stability, and high photoresponse, playing an increasingly important role in systems such as telecommunications, remote sensing, medical diagnostics, optical communication, and biomimetic human vision. Generally, traditional flexible photodetectors consist of three parts: a flexible substrate, conductive electrodes, and a photosensitive material. The flexible substrate determines the device's external mechanical properties, such as bendability, stretchability, and self-healing ability; the conductive electrodes affect the device's characteristics, such as transparency and biodegradability; and the photosensitive material is the decisive factor in the performance of the photodetector. Therefore, the development of high-performance, multifunctional flexible photodetectors requires the synergistic effect of these three components. However, in this study, we use polyvinyl alcohol (PVA) as a solid electrolyte to replace the traditional flexible substrate and conductive electrodes. This combines the components of the flexible photodetector into two, significantly reducing the complexity of its assembly process. This approach promises enormous application potential in wearable electronic devices, smart skin, and portable smartphones. Summary of the Invention:
[0004] The purpose of this invention is to provide a novel method for fabricating a substrate-free, flexible photodetector.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] This invention provides a method for fabricating a substrate-free, flexible photodetector. The method involves preparing MoS2 nanosheets by liquid-phase exfoliation, water bath heating, and vacuum degassing in a polyvinyl alcohol solid electrolyte. The steps include:
[0007] 1) MoS2 was added to a mixed solution of deionized water and ethanol and sonicated. After standing, the supernatant was collected, washed with deionized water, and dried to obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0008] 2) Add the MoS2 nanosheets obtained in step 1) and polyvinyl alcohol (PVA) to a beaker, then add a mixed solution of deionized water and ethylene glycol, and stir evenly with a magnetic stirrer.
[0009] 3) Seal the black turbid solution obtained in step 2), then heat it in a water bath while stirring slowly until the solution becomes a viscous gel. Then remove it, cool it down and let it stand, and then put it into a vacuum chamber for degassing.
[0010] 4) After cooling the sample obtained in step 3), pour the black gel sample into a mold and place it in a vacuum drying oven to dry it under vacuum to form a solid electrolyte.
[0011] According to a preferred embodiment of the present invention, in step 1), 50-100 mL of a mixed solution of deionized water and ethanol (1:1) is uniformly mixed with 100 mg of MoS2 powder, and then ultrasonically treated for 4-6 hours.
[0012] According to a preferred embodiment of the present invention, in step 2), the mass of MoS2 nanosheets is 10-20 mg, the mass of PVA is 1-3 g, the volume of the mixed solution of deionized water and ethylene glycol (1:1) is 15-30 mL, a 30 mL beaker is used, and the uniform stirring time is 10-60 min.
[0013] According to a preferred embodiment of the present invention, in step 3), the water bath heating temperature is 60-100°C, the stirring speed is controlled at 100-300 r / min, the heating time is 1-3 h, and after removal, the vacuum pump is used to evacuate the vacuum for 10-60 min, and then the container is sealed and left to stand overnight.
[0014] According to a preferred embodiment of the present invention, in step 4), the gel is poured into a 4×2×2cm mold and placed in a vacuum drying oven at a vacuum environment of 40-80°C for 12-48 hours, and then taken out for use.
[0015] All equipment and raw materials used in the method of this invention are commercially available products.
[0016] Based on the above technical solution, the present invention has the following advantages:
[0017] (1) This method has the advantages of simple preparation process, short preparation cycle and low preparation cost.
[0018] (2) The substrate-free, flexible photodetector prepared can be used in various semiconductors, metals and other materials with good photoelectric properties.
[0019] (3) The fabrication method of this device can also be extended to the fields of supercapacitors, electrochromic devices, etc. This photodetector has excellent light "on / off" response characteristics, is flexible and bendable, lightweight and easy to carry, and has great potential in the fields of flexible optoelectronic devices, electronic skin and medical care in the future. Attached image description:
[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below:
[0021] Figure 1 This is a schematic diagram of the substrate-free, flexible photodetector fabricated by the invention in Embodiment 4 of this invention.
[0022] Figure 2 This is a physical image of the substrate-free, flexible photodetector fabricated in Example 4 of this embodiment.
[0023] Figure 3 This is a scanning electron microscope (SEM) image of MoS2 before preparation in Example 4 of this embodiment.
[0024] Figure 4 This is a scanning electron microscope (SEM) image of MoS2 in the substrate-free, flexible photodetector prepared in Example 4 of this embodiment.
[0025] Figure 5 This is the Raman spectrum of the MoS2 nanosheets in the substrate-free, flexible photodetector prepared in Example 4 of this embodiment.
[0026] Figure 6 The figure shows the photoelectric response performance (I-T) of the substrate-free, flexible photodetector prepared in Example 4 under different bias voltages.
[0027] Figure 7 The graphs show the photoelectric response performance (I-T) of the substrate-free, flexible photodetector prepared in Example 4 under different light intensities.
[0028] Figure 8 This is a linear scanning voltammetry (LSV) image of the substrate-free, flexible photodetector prepared in Example 4 of this embodiment, under light and dark conditions.
[0029] Figure 9This is a linear scanning voltammetry (LSV) image of the substrate-free, flexible photodetector prepared in Example 5 of this embodiment, under contrasting light and dark conditions.
[0030] Figure 10 This is a physical image of the substrate-free, flexible photodetector fabricated in Example 5 of this embodiment.
[0031] Figure 11 This is a physical image of the substrate-free, flexible photodetector fabricated in Example 6 of this embodiment. Detailed implementation method:
[0032] The present invention will be further described in detail below through specific embodiments, wherein the raw materials are all industrially produced products. These embodiments are for illustrative purposes only and should not be construed as limiting the invention. Modifications or alterations of equivalent forms of the invention by those skilled in the art also fall within the scope defined by the appended claims.
[0033] Example 1:
[0034] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0035] 2) Add 36 mg of MoS2 nanosheet sample (2 mg / mL) and 1 g of PVA obtained in step 1) to a mixed solution of deionized water and ethylene glycol (1:1), and stir for 30 min. 3) Place the well-stirred solution from step 2) into a water bath and heat at 60°C for 2 h.
[0036] The entire water bath process was maintained at a stirring speed of 300 r / min. After heating, the sample was removed and placed in a vacuum drying oven. The vacuum pump was used to evacuate the vacuum for 30 min to obtain a gel sample doped with MoS2 nanosheets after degassing.
[0037] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0038] In embodiment 1 of the present invention, a substrate-free, flexible photodetector that has undergone liquid phase stripping, water bath heating, and vacuum degassing cannot be obtained. This may be because the quality of the added PVA is low, which prevents the formation of a gel. Therefore, a substrate-free, flexible photodetector device cannot be formed in the end.
[0039] Example 2:
[0040] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0041] 2) Add the 36 mg MoS2 nanosheets (2 mg / mL) sample obtained in step 1) and 1.5 g PVA to a mixed solution of 18 mL deionized water and ethylene glycol (1:1), and stir for 30 min.
[0042] 3) Place the well-stirred solution from step 2) into a water bath and heat it at 60°C for 2 hours. Maintain a stirring speed of 300 r / min throughout the water bath process. After heating, remove the solution and place it in a vacuum drying oven. Use a vacuum pump to evacuate the vacuum for 30 minutes to obtain a solution sample doped with MoS2 nanosheets after degassing.
[0043] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0044] In Embodiment 2 of this invention, a mixed solution with a certain viscosity was obtained, but it could not form a semi-solid hydrogel state, thus failing to obtain the target substrate-free, flexible optoelectronic device. This may be because the heating and stirring temperature was insufficient to fully dissolve the PVA and form a high-quality gel. Example 3:
[0045] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0046] 2) Add the 36 mg MoS2 nanosheets (2 mg / mL) sample obtained in step 1) and 1.5 g PVA to a mixed solution of 18 mL deionized water and ethylene glycol (1:1), and stir for 30 min.
[0047] 3) Place the well-stirred solution from step 2) into a water bath and heat it at 95°C for 2 hours. Maintain a stirring speed of 300 r / min throughout the water bath process. After heating, remove the solution and place it in a vacuum drying oven. Use a vacuum pump to evacuate the vacuum for 30 minutes to obtain a solution sample doped with MoS2 nanosheets after degassing.
[0048] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0049] In embodiment 3 of this invention, a mixed solution with a certain viscosity was obtained, but it still could not form a semi-solid hydrogel state. This may be because the content of the added photosensitive material MoS2 nanosheets is too high, which hinders the binding of PVA and water molecules and the formation of a semi-solid hydrogel state, thus making it impossible to obtain the target substrate-free, flexible photodetector device.
[0050] Example 4:
[0051] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0052] 2) Add 18 mg of MoS2 nanosheets (1 mg / mL) obtained in step 1) and 1.5 g of PVA to 18 mL of a mixed solution of deionized water and ethylene glycol (1:1), and stir for 30 min. 3) Place the well-stirred solution from step 2) into a water bath and heat at 95 °C for 2 h.
[0053] The entire water bath process was maintained at a stirring speed of 200 r / min. After heating, the sample was removed and placed in a vacuum drying oven. The vacuum pump was used to evacuate the vacuum for 30 min to obtain a gel sample doped with MoS2 nanosheets after degassing.
[0054] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0055] Figure 4 The images shown are scanning electron microscope (SEM) images of the substrate-free, flexible photodetector obtained by liquid phase exfoliation, water bath heating, and vacuum degassing in Embodiment 4 of this invention. It can be seen that MoS2 is in obvious nanosheet form, indicating that 6 hours of ultrasonication is the optimal ultrasonic time for liquid phase exfoliation. Figure 5 , 6 Figures 7 and 8 show the Raman spectrum of MoS2, the IT performance of the detector under different bias voltages, the IT performance under different light intensities, and a comparison of linear sweep voltammetry (LSV) under illumination and darkness, respectively. These performance tests demonstrate its excellent photoelectric detection performance. Figure 1 , 2 These are schematic diagrams and actual images of a substrate-free, flexible photodetector.
[0056] Example 5:
[0057] 1) Add 1.5g PVA to a mixed solution of 18mL deionized water and ethylene glycol (1:1), and stir for 30min.
[0058] 2) Place the well-stirred solution from step 1) into a water bath and heat it at 95°C for 2 hours. Maintain a stirring speed of 200 r / min throughout the water bath process. After heating, remove the solution and place it in a vacuum drying oven. Use a vacuum pump to evacuate the vacuum for 30 minutes to obtain the degassed gel sample.
[0059] 3) Pour the sample obtained in step 2) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0060] Figure 9 , 10 The figures shown are IT diagrams and physical images of the substrate-free, flexible photodetector obtained in Embodiment 5 of this invention through liquid phase stripping, water bath heating, and vacuum degassing. It can be seen that the photodetector obtained in Embodiment 5 of this invention does not have photoresponse performance because it lacks MoS2 nanosheets as a photosensitive material. PVA itself does not have photoresponse performance. Therefore, the photoelectric device obtained in this case does not have photoelectric performance.
[0061] Example 6:
[0062] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0063] 2) Add 18 mg of MoS2 nanosheets (1 mg / mL) obtained in step 1) and 1.5 g of PVA to 18 mL of a mixed solution of deionized water and ethylene glycol (1:1), and stir for 30 min. 3) Place the well-stirred solution from step 2) into a water bath and heat at 95 °C for 2 h.
[0064] The entire water bath process was maintained at a stirring speed of 300 r / min. After heating, the sample was cooled to obtain a gel sample doped with MoS2 nanosheets.
[0065] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0066] Figure 11The image shows a physical picture of a substrate-free, flexible photodetector obtained by liquid phase stripping, water bath heating, and vacuum degassing in Embodiment 6 of the present invention. It can be seen that the photodetector device obtained in Embodiment 5 of the present invention has a void structure because it was not subjected to vacuum degassing.
[0067] Example 7:
[0068] 1) Dissolve 100 mg of MoS2 powder in 80 mL of deionized water and ethanol (1:1) solution and sonicate for 6 h. Take the supernatant and wash it twice with deionized water. After drying, obtain the exfoliated two-dimensional MoS2 nanosheet sample.
[0069] 2) Add 18 mg of MoS2 nanosheets (1 mg / mL) obtained in step 1) and 1.5 g of PVA to 18 mL of deionized water solution, and stir for 30 min.
[0070] 3) Place the solution stirred in step 2) into a water bath and heat it at 95°C for 2 hours. The stirring speed is maintained at 300 r / min throughout the water bath process. After heating, take it out and place it in a vacuum drying oven. Use a vacuum pump to evacuate the vacuum for 30 minutes to obtain a gel sample doped with MoS2 nanosheets after degassing.
[0071] 4) Pour the sample obtained in step 3) into a 4×2×2cm silicone mold. Place it in a vacuum drying oven and dry it at 60℃ for 24 hours, then remove it for later use.
[0072] Although the sample obtained by liquid phase stripping, water bath heating and vacuum degassing in this embodiment 7 has good flexibility, it lacks ethylene glycol, which results in poor water-locking performance and poor conductivity. Therefore, it cannot be used as a substrate-free, flexible photodetector.
Claims
1. A method for fabricating a substrate-free, flexible photodetector, characterized in that, Includes the following steps: 1) The mixture of deionized water and ethanol in a 1:1 volume ratio was added and ultrasonically treated. After standing, the supernatant was collected, washed twice with deionized water, and dried to obtain the exfoliated two-dimensional... Nanosheet samples; 2) The result obtained in step 1) Nanosheets and polyvinyl alcohol (PVA) were added to a 30 mL beaker, followed by a mixture of deionized water and ethylene glycol in a 1:1 volume ratio. The mixture was then stirred thoroughly with a magnetic stirrer. The nanosheets weigh 10–40 mg, the PVA weighs 1–2 g, the volume of the mixed solution of deionized water and ethylene glycol is 15–30 mL, and the stirring time is 20–40 min. 3) Seal the black turbid solution obtained in step 2), heat it in a water bath while stirring slowly until the solution becomes a viscous gel state, then remove it and place it in a vacuum drying oven, use a vacuum pump to evacuate the vacuum, then seal it and let it cool and stand; wherein, the water bath heating temperature is 50-95℃, the stirring speed is 100-300r / min, the heating time is 1-3h, the vacuum evacuation time is 10-60min, and the sealing and standing time is 12h; 4) Pour the black gel sample obtained after cooling in step 3) into a mold, place it in a vacuum drying oven to dry and solidify it, and obtain a substrate-free, flexible photodetector.
2. The method for fabricating a substrate-free, flexible photodetector according to claim 1, characterized in that, In step 1), 50–100 mL of a mixed solution of deionized water and ethanol is added to 100 mg of... The powder is mixed evenly and then ultrasonically treated for 4–6 hours.
3. The method for fabricating a substrate-free, flexible photodetector according to claim 1, characterized in that, In step 4), pour the gel into Place it in the mold and dry it in a vacuum drying oven at 40-80°C for 12-48 hours, then take it out for later use.
